2 kV Al0.64Ga0.36N-channel high electron mobility transistors with passivation and field plates - Md Tahmidul Alam; Jiahao Chen; Kenneth Stephenson; Md Abdullah-Al Mamun; Abdullah Al Mamun Mazumder; Shubhra S. Pasayat; Asif Khan; Chirag Gupta (Applied Physics Express)
High voltage (∼2 kV) Al _0.64 Ga _0.36 N-channel high electron mobility transistors were fabricated with an on-resistance of ∼75 Ω. mm (∼21 mΩ. cm ^2 ). Two field plates of variable dimensions were utilized to optimize the breakdown voltage. The breakdown voltage reached >3 kV (tool limit) before passivation however it reduced to ∼2 kV after Si _3 N _4 surface passivation and field plate deposition. The breakdown voltage and on-resistance demonstrated a strong linear correlation in a scattered plot of ∼50 measured transistors. The fabricated transistors were electrically characterized and benchmarked against the state-of-the-art high-voltage (> 1 kV) Al-rich (>40%) AlGaN-channel transistors in breakdown voltage and on-resistance, indicating significant progress.